2019
DOI: 10.1038/s41598-019-52350-y
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol S rapidly depresses heart function through estrogen receptor-β and decreases phospholamban phosphorylation in a sex-dependent manner

Abstract: The health effects of the endocrine disruptor Bisphenol A (BPA) led to its partial replacement with Bisphenol S (BPS) in several products including food containers, toys, and thermal paper receipts. The acute effects of BPS on myocardial contractility are unknown. We perfused mouse hearts from both sexes for 15 min with physiologically relevant doses of BPS or BPA. In females BPS (1 nM) decreased left ventricular systolic pressure by 5 min, whereas BPA (1 nM) effects were delayed to 10 min. BPS effects in male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Acute 219 treatment with BPS induced a rapid increase in heart rate in response to catecholamines (Gao et 220 al., 2015). BPS also rapidly depressed left ventricular contraction and myocyte contractility 221 (Ferguson et al, 2019). In both cases, the ERβ antagonist PHTPP abolished BPS actions, 222…”
Section: Bps and Bpf Diminish Katp Channel Activity Via Erβmentioning
confidence: 99%
“…Acute 219 treatment with BPS induced a rapid increase in heart rate in response to catecholamines (Gao et 220 al., 2015). BPS also rapidly depressed left ventricular contraction and myocyte contractility 221 (Ferguson et al, 2019). In both cases, the ERβ antagonist PHTPP abolished BPS actions, 222…”
Section: Bps and Bpf Diminish Katp Channel Activity Via Erβmentioning
confidence: 99%
“…Future areas of interest include: (a) epidemiological or clinical research with additional cardiovascular endpoints—including electrocardiogram or echocardiogram measurements; (b) clinical and experimental work that focuses on vulnerable patient populations—including those with congenital heart defects, cardiomyopathies, or cardiac arrhythmias, as chemical exposures may contribute to cardiovascular dysfunction; (c) clinical and experimental work focused on neonatal, infant and pediatric populations—as cardiac, autonomic and metabolic systems continue to develop and mature after birth; (d) use of (nonrodent) experimental models that better replicate human electrophysiology; (e) studies that explore the effects of bisphenol and phthalate mixtures (or studies that take into account a pediatric patient's “exposome”); and finally, (f) comparative studies that examine the cardiac safety profile of alternative chemicals. The latter is particularly important as we move toward adopting BPA and DEHP substitutes, without a thorough understanding of their safety or impact on cardiovascular health (M. Ferguson, Lorenzen‐Schmidt, & Pyle, 2019; Gao, Ma, Chen, & Wang, 2015; Lozano & Cid, 2013; Trasande, 2017; van der Meer et al, 2014). Through comprehensive examination of bisphenol and phthalate toxicity in vulnerable populations, protective measures or mitigation strategies may be revealed and implemented.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the same group has reported nearly identical effects with BPA-treatment, which suggest that the two chemicals may act via a common mechanism (Yan et al 2011). In a separate study by Ferguson, et al, BPS or BPA-treatment rapidly reduced mechanical function in heart preparations, but slightly different post-translational modifications were observed in myofilament proteins (Ferguson et al 2019). Investigations into the cardiac effects of BPF are even more limited, with a single report noting a decrease in the heart rate of zebrafish following BPF-exposure (Mu et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, many of these alternative chemicals are considered ‘regrettable substitutions’, as BPS and BPF may exert biological effects that are similar to BPA (Kojima et al 2019; Moon 2019; Trasande 2017). To date, it is unclear whether BPA alternatives offer a superior cardiac safety profile, as recent work suggests that BPS and BPF may also impair cardiac function (Ferguson et al 2019; Gao et al 2015; Mu et al 2019). Recent biomonitoring studies have observed an uptick in BPS and BPF exposure in the general population as BPA is phased out and replaced (Lehmler et al 2018), which highlights the urgent need to investigate the impact of BPA analogues on cardiac health.…”
Section: Introductionmentioning
confidence: 99%